Establishing a second-tier panel of 18 ancestry informative markers to improve ancestry distinctions among Asian populations. (July 2019) - Qu, Shengqiu; Zhu, Jing; Wang, Yinji; Yin, Lu; Lv, Meili; Wang, Li; Jian, Hui; Tan, Yu; Zhang, Ranran; Liu, Yuqing; Li, Fei; Huang, Sicheng; et al.
Highlights: 18 new Ancestry informative markers (AIMs) were screened from the 1000 Genomes Project. A novel panel of 18 AIMs can improve ancestry distinctions among Asian populations. Our panel could distinguish the GIH (Gujarati Indian in Houston, TX) from other South Asian groups. Abstract: At present, several mature ancestry informative SNP (AISNP) panels are used to distinguish between continental regions of the world, but a more accurate division within the continent requires a secondary panel to complete. However, many AISNPs for the subgroup ancestry inference are selected from the Kidd Lab panel of 55 AISNPs or other published papers. These panels inevitably lack valuable markers for subgroup ancestry inference. Therefore, instead of choosing from the published panels, we used the 1000 Genomes Project to screen potentially informational markers in Asian populations, including single nucleotide polymorphisms (SNPs) and insertion/deletion polymorphisms (InDels). The allele frequencies of all autosomal SNPs and InDels of the 1000 Genomes Project were compared between 10 populations in Asia to identify markers with the largest pairwise allele frequency differences. Finally, we established a second-tier panel of 18 AIMs in this study, which not only divided the 26 populations of the 1000 Genomes Project into six clusters, but also divided the Asia subgroup into four clusters: Gujarati, East Asia, Southeast Asia and South Asia.